Modulating Oxidative Stress in B Cells Promotes Immunotherapy in Food Allergy. (21st January 2022) - Zeng, Hao-Tao; Liu, Yu; Zhao, Miao; Liu, Jiang-Qi; Jin, Qiao-Ruo; Liu, Zhi-Qiang; Li, Yan; Liu, Zhi-Gang; Feng, Bai-Sui; Yang, Pingchang
Abstract : Allergen-specific immunotherapy (SIT) is the mainstay in the treatment of allergic diseases; its therapeutic efficacy is to be improved. Bacterial flagellin (FGN) has immune regulatory functions. This study investigates the role of FGN in promoting immunotherapy efficacy through modulating oxidative stress in regulatory B cells (Bregs). Blood samples were collected from patients with food allergy (FA) and healthy control (HC) subjects. CD19 + CD5 + Bregs were purified from blood samples by flow cytometry cell sorting. A murine FA model was developed with ovalbumin as the specific antigen. The results showed that peripheral Bregs from FA patients showed lower TLR5-related signals and higher apoptotic activities. The peripheral Breg frequency was negatively correlated with serum FGN levels in FA patients. Exposure to a specific antigen in culture induced antigen-specific Breg apoptosis that was counteracted by the presence of FGN. FGN diminished specific antigen-induced oxidative stress in Bregs. The STAT3/MAPKp38/NF- κ B signal pathway was involved in the FGN/TLR5 signal-promoted superoxide dismutase expression in Bregs. Administration of FGN promotes the SIT efficacy in suppressing experimental FA. In summary, administration of FGN promotes SIT efficacy on FA, suggesting that the combination of FGN and SIT can be a novel therapy that has the translational potential to be employed in the treatment of allergic diseases.